Assessing learners' writing skills in a SLA study: Validating the rating process across tasks, scales and languages. (July 2014) - Huhta, Ari; Alanen, Riikka; Tarnanen, Mirja; Martin, Maisa; Hirvelä, Tuija
There is still relatively little research on how well the CEFR and similar holistic scales work when they are used to rate L2 texts. Using both multifaceted Rasch analyses and qualitative data from rater comments and interviews, the ratings obtained by using a CEFR-based writing scale and the Finnish National Core Curriculum scale for L2 writing were examined to validate the rating process used in the study of the linguistic basis of the CEFR in L2 Finnish and English. More specifically, we explored the quality of the ratings and the rating scales across different tasks and across the two languages. As the task is an integral part of the data-gathering procedure, the relationship of task peformance across the scales and languages was also examined. We believe the kinds of analyses reported here are also relevant to other SLA studies that use rating scales in their data-gathering process.